Immune or inherited thrombocytopenia? A population-based cohort study on children and adolescents presenting with a low platelet count - Kulmala, Lauri-Matti; Aarnivala, Henri; Pokka, Tytti; Huurre, Anu; Järvelä, Liisa; Palmu, Sauli; Pöyhönen, Tuuli; Niinimäki, Riitta (WILEY, 2025)
Background
Thrombocytopenia is a common hematologic finding in children and adolescents. Immune thrombocytopenia (ITP) is the most common cause of this finding, but the differential diagnosis includes a growing list of genetic disorders. We aimed to report differences in phenotypes of patients with ITP, inherited platelet disorder (IPD)/primary immunodeficiency disorder (PID), and other causes, with a focus on differentiating ITP from inherited thrombocytopenia.
Procedure
This retrospective, population-based observational cohort from 2006 to 2020 involved 506 Finnish children under 16 years of age presenting with isolated thrombocytopenia.
Results
Of the 506 participants, 79.7% had ITP, 6.7% had IPD/PID, and 13.6% had other causes of thrombocytopenia. A platelet count of <= 12 x 109/L best distinguished between ITP and other reasons with a sensitivity of 60% and a specificity of 80%. Among patients with the lowest platelet count of less than 10 x 109/L, 95.9% had ITP, 3.3% had IPD/PID, and 0.8% had other causes. Severe bleeding events were reported in 20 patients (4.0%), but there were no cases of intracranial or fatal bleeding due to thrombocytopenia. Up to 50% of patients with a high suspicion of inherited thrombocytopenia remained without a specific diagnosis despite genetic testing.
Conclusions
ITP remains the most common cause of thrombocytopenia. A platelet count of <= 12 x 109/L often leads to an ITP diagnosis. Genetic disorders are rare but should be suspected in patients with persisting thrombocytopenia, especially with platelet counts constantly above 12 x 109/L, a positive family history, or atypical clinical features.